2020
DOI: 10.1038/s41398-020-00913-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychological health, sleep quality, and coping styles to stress facing the COVID-19 in Wuhan, China

Abstract: To understand Wuhan residents’ psychological reactions to the COVID-19 epidemic and offer a reference point for interventions, an online questionnaire survey was conducted. It included the Disorder 7-Item Scale (GAD-7), the Patient Health Questionnaire 9-Item Scale (PHQ-9), Athens Insomnia Scale, and Simplified Coping Style Questionnaire. Categorical data were reported as numbers and percentages. Multivariate logistic regression models were used to evaluate the association between demographic factors and anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
336
8
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(392 citation statements)
references
References 32 publications
38
336
8
10
Order By: Relevance
“…These results support the ndings reported by Al-Hanawi et al [22] that respondents' level of worry or concern attributed to COVID-19 differs signi cantly across gender and educational level. This result is also in line with previous studies [23,24] carried out in China, indicating that females have higher levels of anxiety compared to males. Similarly, the respondents' level of self-reported preventive behaviour signi cantly differed according to their gender, occupation, years of working experience, and educational level.…”
Section: Discussionsupporting
confidence: 93%
“…These results support the ndings reported by Al-Hanawi et al [22] that respondents' level of worry or concern attributed to COVID-19 differs signi cantly across gender and educational level. This result is also in line with previous studies [23,24] carried out in China, indicating that females have higher levels of anxiety compared to males. Similarly, the respondents' level of self-reported preventive behaviour signi cantly differed according to their gender, occupation, years of working experience, and educational level.…”
Section: Discussionsupporting
confidence: 93%
“…These results support results reported by Al-Hanawi et al [22] that respondents' level of worry due to COVID-19 differs signi cantly across gender and educational level. The result also in line with a previous studies [23,24] in China, which indicated that females have high levels of anxiety compared to males. Similarly, the respondents' level of self-reported preventive behaviour signi cantly differed according to their sex, occupation, years of working experience and educational level.…”
Section: Discussionsupporting
confidence: 92%
“…Two other studies again from China reported that 27.5% and 31.6% had anxiety, 29.3% and 27.9% had depression, 30.0% had a sleep disorder or 29.% insomnia, 24,4% acute stress and 29.8% had a passive response to COVID-19. Female gender and being married have been identified as a risk factor for anxiety ( Fu et al, 2020 ; Shi et al, 2020 ). A study from Turkey reported 23.6% depression and 45.1% anxiety ( Ozdin and Bayrak Ozdin, 2020 ).…”
Section: Discussionmentioning
confidence: 99%